Data ingestion pipeline and data marts to empower UK researchers, academics, and business and economic decision makers - Yu, Qicheng; Healy, Stephanie; Ravi, Indrajitrakuraj; Patel, Preeti (2021)
The data integration problem from the voluminous data generated from different sources in disparate formats coupled with a large number of diverse requirements related to the data have made the need for a reconciliation of them into a unique model, the identification of relationships, and the enabling of data analytics processes extremely vital. In light of the unabated growth of data volume and the need for data sharing across various stakeholders there is a requirement for the design and implementation of a data ingestion pipeline with a set of data marts. In this paper, we present a data ingestion pipeline which empowers hitherto impeded data users to easily access shared big data sources. We aim to improve the effectiveness and efficiency of open 993source data sharing capability so that researchers, academics, policy makers, businesses and government departments can all benefit from the use of these sophisticated data management techniques. In this work, we propose a novel data ingestion pipeline and data marts approach to utilise data generated from big data systems and effectively integrate them to a unified form, ready for use. Currently, the data ingestion pipeline focuses on UK data, as our primary aim is to support the City of London and the various communities within it. An additional benefit is the potential for developing collaboration across disciplines to tackle the economic and social challenges faced by cities in innovative ways.